Conversations with Jim Harrison - Harrison, Jim 1937-2016 (University Press of Mississippi, 2019)
"Conversations with Jim Harrison, Revised and Updated offers a judicious selection of interviews spanning the writing career of Jim Harrison (1937-2016) from its beginnings in the 1960s to the last interview he gave weeks before his death in March 2016. Harrison labeled himself and lived as a "quadra schizoid" writer. He worked in fiction, poetry, nonfiction, and screenwriting, and he published more than forty books that attracted an international following. These interviews supply a lively narrative of his progress as a major contemporary American author. This collection showcases Harrison's pet peeves, his candor and humility, his sense of humor, and his patience. He does not shy from his authorial obsessions, especially his efforts to hone the novella, for which he is considered a contemporary master, or the frequency with which he defied polite narrative conventions and created memorable, resolute female characters. Each conversation attests to the depth and range of Harrison's considerable intellectual and political preoccupations, his fierce social and ecological conscience, his aesthetic beliefs, and his stylistic orientations in poetry and prose." ... Provided by publisher
Includes bibliographical references and index
Originally published. - Jackson : University Press of Mississippi, 2002
Keywords: Harrison, Jim -- 1937-2016 -- Interviews; Harrison, Jim -- 1937-2016; Interviews / lcgft; Authors, American -- 20th century -- Interviews; Interview